Dicrostonyx torquatus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Dicrostonyx torquatus (Pallas, 1778). Nova Spec. Quad. Glir. Ord., p. 206. REVIEWED BY: M. Andera (MA). TYPE LOCALITY: U.S. S. R., R.S.F.S. R., mouth of Ob River. DISTRIBUTION: Palearctic tundra from White Sea to Chukotka (U.S. S.R.), Novaya Zemlya, and New Siberian Isis. COMMENT: Formerly included groenlandicus and vinogradovi; see Corbet, 1978:96, but see Rausch, 1977, in Sokolov, ed., [Adv. Mod. Theriol.], Acad. Sci. U.S. S. R., Nauka, Moscow, pp. 162- 177, who considered them distinct species. Includes chionopaes which may be a distinct species; see Gileva, 1975, Dokl. Akad. Nauk, 224:697-700, Gileva, 1980:99- 103, in Vorontsov and Van Brink, eds., Animal genetics and evolution, Junk, The Hague, and Kozlovskii, 1974, Dokl. Akad. Nauk S.S.S.R., 219:981-984. See also comments under genus Dicrostonyx. ISIS NUMBER: 5301410008073002001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 483, DOI: 10.5281/zenodo.7353034